2004
DOI: 10.1682/jrrd.2004.02.0139
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of four electrical stimulation types on Staphylococcus aureus growth in vitro

Abstract: We evaluated the efficacy of common electrical stimulation (ES) types on bacterial growth in vitro using clinically relevant conditions. Four types of ES-continuous microamperage direct current (µADC), high-voltage pulsed current (HVPC), low-voltage monophasic milliamperage pulsed current (LVMmAPC), and low-voltage biphasic milliamperage pulsed current (LVBmAPC)-were each applied to a separate set of culture plates containing Staphylococcus aureus for 1 h at 37 ºC on three consecutive days. After ES treatment,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 21 publications
(50 reference statements)
1
31
0
1
Order By: Relevance
“…Drees et al showed that direct electrical current of 25 to 350 mA applied to planktonic suspensions of P. aeruginosa or E. coli resulted in a significant reduction in viable cells (28). In addition, Merriman et al tested four different electrical stimulation types, continuous microamperage direct current, high-voltage pulsed current, low-voltage monophasic milliamperage pulsed current, and low-voltage biphasic milliamperage pulsed current on culture plates containing S. aureus (29). These researchers found that microamperage direct current and highvoltage pulsed current had significant inhibitory effects, while the other two electrical stimulation types did not (29).…”
Section: Discussionmentioning
confidence: 99%
“…Drees et al showed that direct electrical current of 25 to 350 mA applied to planktonic suspensions of P. aeruginosa or E. coli resulted in a significant reduction in viable cells (28). In addition, Merriman et al tested four different electrical stimulation types, continuous microamperage direct current, high-voltage pulsed current, low-voltage monophasic milliamperage pulsed current, and low-voltage biphasic milliamperage pulsed current on culture plates containing S. aureus (29). These researchers found that microamperage direct current and highvoltage pulsed current had significant inhibitory effects, while the other two electrical stimulation types did not (29).…”
Section: Discussionmentioning
confidence: 99%
“…The effect of electrical stimulation (ES) has been tested in vitro on different types of cells involved in wound healing, such as macrophages,9 fibroblasts,1014 epidermal cells,1520 bacteria,2123 and endothelial cells2426 that have demonstrated changes in cell migration, proliferation, and orientation, increase in proteins and DNA synthesis, and antibacterial effects. When applied on in vivo models2740 and clinical stud ies,4161 EST has shown positive effects on wound closure and healing rate.…”
Section: Introductionmentioning
confidence: 99%
“…There was no noticeable corrosion and coloration on the Nickel or Nichrome wire electrodes by examined using naked eye while using stainless steel wire show some physical effects in previous study [19] but more tests needed to find the exact amount of corrosion if any.…”
Section: Discussionmentioning
confidence: 71%